Studi Pemantauan Penurunan Muka Tanah di Cekungan Bandung dengan Metode Survei GPS dan InSAR - Irwan Gumilar; Hasanuddin Z. Abidin; L.M. Hutasoit; D.M. Hakim; Dina A. Sarsito; H. Andreas; Teguh P. Sidiq (Indonesian Journal of Geospatial, 2012)
Abstract. Land subsidence is a phenomena that has been commonly occurs in big cities around the world. Especially in Indonesia, Bandung as the one of big cities in Indonesia, has been identified for land subsidence. This land subsidence is suspected to ground water explotation by the factories which are located around Bandung basin. Land subsidence has caused many problems, such as damage to houses, buildings, and infrastructures (roads, bridges, etc.), and as the most serious problem is that land subsidence can increase the size of areas susceptible for flooding. In 2010 was noted that for almost the whole year, in the south Bandung experienced a terrible flood. Seeing the causes which is caused by land subsidence, it is a necessary to do charachteristic mapping of land subsidence. As one of the method that will be use for monitorizing the land subsidence is using GPS (Global Positioning System) survey and InSAR (Interferometry Synthetic Aperture Radar). In this paper, will be explained about land subsidence that occur in Bandung from GPS data. Keywords : GPS, groundwater, InSAR, land subsidence.